2007
DOI: 10.1111/j.1460-2695.2007.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology to guarantee the structural integrity of Al2O3/SiC composite using crack healing and a proof test

Abstract: A B S T R A C T Structural ceramics are brittle and sensitive to flaws. As a result, the structural integrity of a ceramic component may be seriously affected by inherent flaws. Self-crack-healing is an excellent answer to this problem. At the moment, however, there is no technique to heal embedded flaws. Therefore, a technique to guarantee the reliability of ceramic components is demanded, and thus a technique using crack healing followed by proof test was developed by K. Ando et al. to accomplish this. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…According to previous studies [3,4], 15 vol.% fraction of SiC was sufficient for filling the surface crack with 100 m and attain full strength recovery of alumina/SiC composite. Assuming the local crack facing distance of the induced indentation cracks to be the same one can argue that the optimal volume fraction of TiC selfhealing agent should be of the order of 30 vol.% in order to realize a comparable self-healing of TiC/alumina composite and to compensate for the lower RVE value.…”
Section: Relative Volume Expansion (Rve)mentioning
confidence: 96%
See 1 more Smart Citation
“…According to previous studies [3,4], 15 vol.% fraction of SiC was sufficient for filling the surface crack with 100 m and attain full strength recovery of alumina/SiC composite. Assuming the local crack facing distance of the induced indentation cracks to be the same one can argue that the optimal volume fraction of TiC selfhealing agent should be of the order of 30 vol.% in order to realize a comparable self-healing of TiC/alumina composite and to compensate for the lower RVE value.…”
Section: Relative Volume Expansion (Rve)mentioning
confidence: 96%
“…However, they also noted that the formed SiO 2 could not seal the pre-cracks fully due to the low SiC particle content. Ando et al were the first to report in detail on the self-healing behaviour of SiC particles containing alumina matrix composites as a function of temperature and annealing time [3][4][5]. It was shown that alumina/15 vol.%-SiC composites can attain a complete strength recovery by annealing in air at 1300 • C for 1 h or at 1200 • C for 10 h [3].…”
Section: Introductionmentioning
confidence: 96%
“…Figure 20 shows the data on the fracture stress of the crack-healed and the proof-tested specimens as a function of temperature with the evaluated σ G for the crack-healed alumina/20 vol% SiC particles composite when σ p = 435 MPa (Ono et al, 2007). Except the data at 1373 K, all specimens have higher strength than the σ G at all temperatures.…”
Section: Room Temperaturementioning
confidence: 99%
“…Of course, the required minimal temperature to trigger the healing reaction depends primarily on the chemical stability of the healing material in an oxygen-containing environment. This dependence has already been demonstrated (but apparently not been appreciated) in the combined first-generation studies on self-healing of Al 2 O 3 or Si 3 N 4 filled with SiC or Ni particles [3][4][5][6][7]. In these studies, the crack healing ability was studied as a function of both temperature (from 900 to 1400°C) and time (between 1 and 300 h) and widely different values were obtained for different particle sizes.…”
Section: Introductionmentioning
confidence: 96%